Implementasi Manajemen Kesiswaan untuk Meningkatkan Kualitas Akademik Peserta Didik di SMP IT At-Thohiriah - M Najmudin Rahmatullah; Imam Tholkhah; Amie Primarni (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2020)
Management is a process of activities that are planned and carried out intentionally and continuously to all students in the relevant educational institutions in order to be able to participate in the learning and teaching process effectively and efficiently. Learning achievement is the level of humanity students have in accepting, rejecting and assessing the information obtained in the teaching and learning process. A person's learning achievement is in accordance with the level of success of something in learning subject matter which is expressed in the form of grades or report cards for each field of study after experiencing the teaching and learning process. This study aims to determine the extent of implementation, acceptance, student management, efforts made, as well as the implications of the application of student management in At-Thiriiriah Junior High School in improving the quality of students. This study uses a qualitative approach using a type of case study research by taking a background in At-Thiriahah Junior High School, Gunung Bunder I, Pamijahan, Bogor. Data collection is done by interview, observation and documentation. Data analysis uses descriptive analysis method. Based on the process of data collection and data analysis, researchers can conclude several things including: (1) The application of student management that takes place at At-Thiriahah IT Junior High is classified as good, where the concept of student management starts from the planning and implementation of new students, monitoring or control and evaluation can be applied by all at IT Thohiriah Junior High School. (2) In an effort made by schools related to student management to improve the quality of students in At-Thiriahah Junior High School, among others: improving discipline including a). At-Thiriahah Junior High School students arrive at 07.00 WIB, b) Wearing Uniforms. (3) As for the implications of the implementation of student management to improve the quality of students in At-Thiriah Gunung Bunder I Junior High School, seen from the academic achievement in the form of UN scores that have increased, non-academic achievements achieved by At-Thiriahah IT Middle School students have also increased, and graduates of At-Thiriiriah IT Middle School were accepted into public and private schools. Keywords: Student Management, Academic Quality of Students